Pemberdayaan Ekonomi Masyarakat dengan Literasi dan Pengelolaan Sumber Daya Lokal di Desa Perkebunan Maryke - Yassin Azhim Rantissi (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Community economic empowerment is a strategic step in improving welfare and economic independence, especially in areas rich in local resources. Economic literacy plays a crucial role in this process, as it provides communities with the knowledge and skills to understand and manage resources efficiently and sustainably. This article examines efforts to empower communities economically through the enhancement of literacy and the management of local resources. With an economic literacy approach that covers aspects of financial management, business operations, and marketing, communities can maximize the potential of local resources to create added economic value. This study highlights various forms of local resources, such as agricultural products, fisheries, and handicrafts, and their potential to drive local economic growth. The analysis shows that good economic literacy not only improves the community's ability to make informed economic decisions but also contributes to poverty reduction and overall improvement in the quality of life. Therefore, empowerment through literacy and local resource management is key to achieving inclusive and sustainable economic development.